Mediator Complex Subunit MED1 Protein Expression Is Decreased during Bladder Cancer Progression - Klümper, Niklas; Syring, Isabella; Vogel, Wenzel; Schmidt, Doris; Müller, Stefan C.; Ellinger, Jörg; Adler, David; Brägelmann, Johannes; Perner, Sven (Frontiers in Medicine, 2017)
Introduction Bladder cancer (BCa) is among the most frequent cancer entities and relevantly contributes to cancer-associated deaths worldwide. The multi-protein Mediator complex is a central regulator of the transcriptional machinery of protein-coding genes and has been described to be altered in several malignancies. MED1, a subunit of the tail module, was described to negatively modulate expression of metastasis-related genes and to be downregulated in melanoma and lung cancer. In contrast, MED1 hyperactivity was described in breast and prostate cancer, likely due its function as a hub for nuclear hormone receptors. So far, only little is known about the function of the Mediator complex in BCa. The aim of this study was therefore to investigate the role of MED1 in BCa as a prognostic biomarker and a biomarker of disease progression. Methods The protein expression of MED1 was assessed by immunohistochemistry (IHC) on tissue microarrays from 224 patients: benign urothelium n=31, non-muscle invasive BCa (NMIBC; pTis, pT1) n=72, and muscle invasive BCa (MIBC; pT2-T4) n=121. Comprehensive clinicopathological information including follow-up were available. Quantification of MED1 protein expression was evaluated by the semi-quantitative image analysis program Definiens. Results MED1 expression significantly decreased during BCa progression from benign urothelium to advanced BCa. Muscle invasion, the crucial step in BCa progression, was associated with low MED1 protein expression. Accordingly, decreased MED1 expression was found in primary BCa samples with positive lymphonodal status and distant metastases. Furthermore, cancer specific survival was significantly worse in the group of low MED1 expression. Conclusion Our findings show that the downregulation of MED1 is associated with muscle invasion, metastatic spread and shorter overall survival in BCa.